Users’ perceptions about receiving personalized depression risk information: findings from a qualitative study - Eccles, Heidi; Nadouri, Doaa; Nannarone, Molly; Lashewicz, Bonnie; Schmitz, Norbert; Patten, Scott B.; Manuel, Douglas G.; Wang, JianLi (Université d'Ottawa | University of Ottawa, 2021)
Abstract Objectives To understand users’ perceptions about receiving their personalized depression risk score and to gain an understanding about how to improve the efficiency of risk communication from the user perspective. Methods A qualitative study embedded in a randomized controlled trial (RCT) on evaluating the impact of providing personalized depression risk information on psychological harms and benefits. The participants (20 males and 20 females) were randomly selected from the intervention arm of the RCT after the 12-month assessment. The qualitative interviews were conducted through telephone, audio recorded and transcribed verbatim. We conducted a content analysis to describe the content and contextual meaning of data collected from participants. Results The first theme explained the motivation for receiving a risk score. Most participants chose to receive their personalised depression risk score with the goal of improving their self-awareness. The results revealed three sub-themes surrounding perceptions and implication of receiving their risk score: positive, negative, and neutral. Most participants found that receiving their score was positive because it improved their awareness of their mental health, but some participants could see that some people would have negative feelings when getting the score causing them to be more likely to get depression. The final theme focussed on improvements including: the best delivery methods, having resources and strategies, and targeting younger people. Conclusion The most significant motivation for, and benefit of receiving one’s personalized depression risk score was improved awareness of one’s mental health. A comprehensive risk communication program may improve the uptake and maximize the impact on behavior changes and risk reduction.